The interaction between the soluble programmed death ligand-1 (sPD-L1) and PD-1+ regulator B cells mediates immunosuppression in triple-negative breast cancer - Li, Xuejiao; Du, Huan; Zhan, Shenghua; Liu, Wenting; Wang, Zhangyu; Lan, Jing; PuYang, Longxiang; Wan, Yuqiu; Qu, Qiuxia; Wang, Sining; Yang, Yang; Wang, Qin; et al. (Frontiers in Immunology, 2022)
Accumulating evidence suggests that regulatory B cells (Bregs) play important roles in inhibiting the immune response in tumors. The PD-1 and PD-L1 were important molecules to maintains the balance of the immune response and immune tolerance. This study is aimed to evaluate the soluble form of PD-L1 and its function on inducing the differentiation of B lymphocytes, investigate the relationship between sPD-L1 and B cells subsets, and explore antitumor activity of T lymphocytes after PD-L1 blockade in co-culture systems. In an effort to explore the role of sPD-L1 in human breast cancer etiology, we examined the levels of sPD-L1 and IL-10 in serum of breast tumor patients, the proportion of B cells, PD-1+ B cells, Bregs and PD-1+ Bregs in peripheral blood of patients with breast tumor, and assessed their relationship among sPD-L1, IL-10 and B cell subsets. The levels of sPD-L1 and IL-10 in serum were found significantly higher in breast cancer (IBCa) patients than those in breast fibroadenoma tissues (FIBma) patients. Meanwhile, the proportions of PD-1+ B cells, Bregs and PD-1+ Bregs in peripheral blood of IBCa patients were significantly higher than those of FIBma patients. Notably, they were the highest in TNBC among other subtypes of IBCa. And the positive correlation of sPD-L1 and IL-10, IL-10 and PD-1+ Bregs, sPD-L1 and PD-1+ Bregs were observed in IBCa. We further demonstrated that sPD-L1 could induce Bregs differentiation and IL-10 mRNA expression in a dose-dependent manner in vitro. Finally, we showed that the induction of Regulatory T cells by Bregs was further shown to suppress antitumor response, and PD-L1 blockade therapies could promote the apoptosis of tumor cells. Together, these results indicated that sPD-L1 and PD-1+ Bregs in breast cancer, could mediate the differentiation of Bregs, expand of CD4+ Tregs and weaken of antitumor activity of CD4+ T cells. The PD-L1/PD-1 blockade therapies might be powerful theraputic strategy for IBCa patients, particular for TNBC patients with high level of PD-1+ Bregs.